La aglomeración y la elección de localización de la inversión extranjera directa: nueva evidencia de la IED en manufacturas en México - Jordaan, Jacob A. (El Colegio de México, A.C., 2012)
In this paper, I estimate conditional logit location models to identify the regional characteristics that influenced the location choice of the large influx of manufacturing FDI into Mexico that occurred in the second half of the 1990s following the creation of NAFTA. The main findings of the analysis are three-fold. First, regional demand, labor costs, labor quality, agglomeration economies and regional distance to Mexico City and the US are all important location factors. Second, findings indicate that the location decision of export-oriented firms is not affected by regional demand. Third, I find evidence that agglomeration economies have a spatial dimension.